The impact of oxidative mouthwash on microleakage of composite restorations: A stereomicroscopic study - Farnaz Farahat; Mehrad Karimi; Tayebe Sadat Baghaei Ardakani; Zahra Shevidi (Mashhad University of Medical Sciences, 2023)
Objective: Although oxidative mouthwashes have many antimicrobial benefits, it has been suggested that residual oxygen interferes with composite resin adhesion to dental structures. This study aimed to evaluate the effect of an oxidative mouthwash on the microleakage of composite restorations.Methods: Twenty-four extracted human third molars were randomly assigned into three groups: Group 1: a 0.05% sodium fluoride mouthwash, Group 2: an oxidative mouthwash, and Group 3: distilled water. The teeth were immersed in the corresponding solution for 10 minutes a day over 14 days. Class V cavities were prepared in the buccal and lingual surfaces of the teeth (n=15 per group) and restored with Filtek Z250 composite. The teeth were thermocycled between 5º C and 55º C for 1000 cycles, then immersed in 2% fuchsin solution for 24 hours, followed by sectioning in the bucco-lingual direction. The gingival and occlusal microleakage were inspected using a stereomicroscope. Data were analyzed using Kruskal-Wallis and Mann-Whitney U tests. The statistical significance level was considered at P 0.05.Results: The highest and lowest average microleakage scores were observed at the gingival and occlusal margin of cavities immersed in the sodium fluoride mouthwash, respectively. No statistical differences were observed in microleakage among the three groups either at the occlusal or at the gingival margin (P>0.05). The Mann-Whitney U test showed a statistically greater microleakage at the cervical (1.05±1.1) compared to the occlusal (0.694±0.53) margins, irrespective of the treatment groups (P=0.033).Conclusions: Using an oxidative mouthwash does not affect the microleakage of composite restorations